The Epidemiology of Herpes Simplex Virus Eye Disease in Northern California. (December 2014) - Stanzel, Tisha Prabriputaloong; Diaz, Jose D.; Mather, Rookaya; Wong, Ira G.; Margolis, Todd P.; Gritz, David C.
Abstract Purpose: To calculate the incidence and prevalence of herpes simplex virus (HSV) eye disease in a large, well-defined population in Northern California, USA, and to determine the recurrence rate following an initial episode of disease in this cohort. Methods: A retrospective, observational, cohort study using population-based data and medical record review. The patient database of a large, regional health maintenance organization (Northern California Kaiser Permanente) was searched, and the study population consisted of 1, 042, 351 people over a 1-year study period from 1 July 1998 through 30 June 1999. Only ocular HSV cases with definitive clinical or laboratory confirmed diagnoses were included. Active and inactive cases were included, however only active cases were used in incidence and prevalence calculations. Bilateral disease was counted as one case. Newly diagnosed cases were followed for recurrence from initial presentation through 31 December 2002. Results: After chart review of 322 possible cases, 71 new cases and 59 previously diagnosed active cases of ocular HSV were confirmed. This resulted in an incidence rate of 6.8 new cases/100, 000 person-years (95% confidence interval, CI, 5.3–8.6). Incidence increased with age, and rates were highest in people over 75 years of age (p < 0.001). The recurrence rate in new cases was 18% for the 3-year follow-up time, and was equal to 5% per year (95% CI 3–9%). Conclusion: The incidence and prevalence of ocular herpes simplex in this study was lower than previously reported. Incidence increased with age, and there were significantly higher rates in the older population.